Transcriptomic and Proteomic Analysis of Shaan2A Cytoplasmic Male Sterility and Its Maintainer Line in Brassica napus - Ning, Luyun; Wang, Hao; Li, Dianrong; Lin, Zhiwei; Li, Yonghong; Zhao, Weiguo; Chao, Hongbo; Miao, Liyun; Li, Maoteng (Frontiers in Plant Science, 2019)
Cytoplasmic male sterility (CMS) lines are widely used for hybrid production in Brassica napus. The Shaan2A CMS system is one of the most important in China and has been used for decades; however, the male sterility mechanism underlying Shaan2A CMS remains unknown. Here, we performed transcriptomic and proteomic analysis, combined with additional morphological observation, in the Shaan2A CMS. Sporogenous cells, endothecium, middle layer, and tapetum could not be clearly distinguished in Shaan2A anthers. Furthermore, Shaan2A anther chloroplasts contained fewer starch grains than those in Shaan2B (a near-isogenic line of Shaan2A), and the lamella structure of chloroplasts in Shaan2A anther wall cells was obviously aberrant. Transcriptomic analysis revealed differentially expressed genes (DEGs) mainly related to carbon metabolism, lipid and flavonoid metabolism, and the mitochondrial electron transport/ATP synthesis pathway. Proteomic results showed that differentially expressed proteins were mainly associated with carbohydrate metabolism, energy metabolism, and genetic information processing pathways. Importantly, nine gene ontology categories associated with anther and pollen development were enriched among down-regulated DEGs at the young bud (YB) stage, including microsporogenesis, sporopollenin biosynthetic process, and tapetal layer development. Additionally, 464 down-regulated transcription factor (TF) genes were identified at the YB stage, including some related to early anther differentiation such as SPOROCYTELESS (SPL, also named NOZZLE, NZZ), DYSFUNCTIONAL TAPETUM 1 (DYT1), MYB80 (formerly named MYB103), and ABORTED MICROSPORES (AMS). These results suggested that the sterility gene in the Shaan2A mitochondrion might suppress expression of these TF genes in the nucleus, affecting early anther development. Finally, we constructed an interaction network of candidate proteins based on integrative analysis. The present study provides new insights into the molecular mechanism of Shaan2A CMS in B. napus.